Implementasi Web Commerce Sebagai Media Pelatihan Kewirausahaan Mahasiswa - Safii, M. (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2017)
This study proposes a dynamic web-based information system using a content management system (CMS) osCommerce with PHP programming language and MySQL database. Utilization of a dynamic web Content Management System has advantages of easy and friendly in content management. Realtime information dissemination network using the Internet will bring up a quick response from the customer as the target market so that the main goal of entrepreneurial activity is achieved. With the implementation of web commerce information system is expected to be a solution for students as a means of self-employment training that has relevance to the subject so that students will have confidence in the start up of entrepreneurial activity as an effort to create their own jobs for students.